Analysis of filament arrangements and generation of statistically equivalent composite micro-structures - Gommer, Frank; Endruweit, Andreas; Long, Andrew C. (Elsevier, 2014)
An efficient method to describe and quantify the filament arrangement in fibre bundles based on the analysis of micrographs was developed. Quantitative measurement of relative filament positions indicated that the initially random arrangement of filaments shows increasingly strong characteristics of square and hexagonal configurations with increasing level of transverse compaction. An existing micro-structure generator was extended to incorporate the measured data allowing statistically equivalent filament arrangements to be generated at any fibre volume fraction. These can be used to determine micro-structural properties of actual fibre reinforced composites.